Pulping of Hibiscus sabdariffa Linn. (Roselle) - Guha, S. R. D.; Sharma, Y. K.; Dhoundiyal, S. N. (Indian Forester, 1978)
The paper reports The results on soda pulping of Hibisucus subdariffa Linn (Roselle), The average fibre length of bast fibre was 305 mm, fibre diameter-21.91 Î¼ and cell wall thickness 5.6 Î¼ The woody portion had an average fibre length of 0.799 mm, fibre diameter of 32.1 Î¼. And cell wall thickneso of 2.9 Î¼. Soda pulps in good yield and satisfactory properties could be prepared in laboratory. Pilot Plant scale trial confirmed laboratory finding. Pulping of bast fibre along, woody portion and whole plant indicated that yield of bast portion and woody portion was more or less same. The strength properties of bast pulp were higher.